2014
DOI: 10.3389/fnbeh.2014.00002
|View full text |Cite
|
Sign up to set email alerts
|

The neural correlates of risk propensity in males and females using resting-state fMRI

Abstract: Men are more risk prone than women, but the underlying basis remains unclear. To investigate this question, we developed a trait-like measure of risk propensity which we correlated with resting-state functional connectivity to identify sex differences. Specifically, we used short- and long-range functional connectivity densities to identify associated brain regions and examined their functional connectivities in resting-state functional magnetic resonance imaging (fMRI) data collected from a large sample of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 81 publications
6
34
0
Order By: Relevance
“…On a side note, when investigating sex differences in a group of younger adults (around 30 years of age) females show a similar pattern of brain activity to the older adults and tended to make more risk aversive choices following loss-related feedback compared to males (Lee, Chan, Leung, Fox & Gao, 2009). Females tend to be risk averse compared to males (Powell & Ansic, 1997;Zhou et al, 2014) which is the same pattern of behaviour shown by older vs. younger adults. Given the role of these regions in risk aversion and decision-making, greater activation within the OFC and insula within these groups potentially underpins a general risk-aversive decisionframework (Depping & Freund, 2011;Depping & Freund, 2013;Zhou et al, 2014).…”
Section: Despite Older Adults Engaging the Same Network Of Brain Areasupporting
confidence: 53%
See 1 more Smart Citation
“…On a side note, when investigating sex differences in a group of younger adults (around 30 years of age) females show a similar pattern of brain activity to the older adults and tended to make more risk aversive choices following loss-related feedback compared to males (Lee, Chan, Leung, Fox & Gao, 2009). Females tend to be risk averse compared to males (Powell & Ansic, 1997;Zhou et al, 2014) which is the same pattern of behaviour shown by older vs. younger adults. Given the role of these regions in risk aversion and decision-making, greater activation within the OFC and insula within these groups potentially underpins a general risk-aversive decisionframework (Depping & Freund, 2011;Depping & Freund, 2013;Zhou et al, 2014).…”
Section: Despite Older Adults Engaging the Same Network Of Brain Areasupporting
confidence: 53%
“…Activity with the orbitofrontal cortex (OFC) was increasingly bilateral in older vs. younger adults. The OFC has been reliably associated with risky decision-making (Jollant et al, 2010), notably the integration of emotion into decision-making frameworks (Wallis, 2007) and has been linked to risk propensity (Zhou et al, 2014). Furthermore, older adults expressed more activity within the right insula compared to younger adults, an area involved in risk processing, notably risk aversion tendencies (Kuhnen & Knutson, 2005).…”
Section: Despite Older Adults Engaging the Same Network Of Brain Areamentioning
confidence: 99%
“…Six ICNs were chosen as networks of interest due to their previously reported implication in decision making and relat ed processes (frontal, default mode, left and right frontoparietal, cingulo-opercular, and basal ganglia networks; Davis et al, 2013;Shannon et al, 2011;Tom et al, 2007;Zhou et al, 2014). The resulting participant-specific maps of every network were concatenated across participants and saved in 4D files.…”
Section: Generation Of Intrinsic Connectivity Networkmentioning
confidence: 99%
“…Moreover, our sample was restricted to male participants. Existing studies have described remarkable gender differences in risk-seeking behaviors (Ball et al, 1984) and associated neg ative consequences (Turner & McClure, 2003), but, to date, only the study of Zhou et al (2014) has addressed gender functional connectivity differences linked to risk-seeking be havior. Therefore, we believe that future decision-making re search will benefit from the inclusion of both genders and different age ranges.…”
Section: Limitationsmentioning
confidence: 99%
“…The functional roles of the aINS and the NAc are parallel to the processing of pain and pleasure1719, which are major motivators for medical care-seeking. Furthermore, the variation in intrinsic brain signatures, including resting-state (rs) functional connectivity (FC) and grey matter volume (GMV), is associated with the individual differences in risk-taking tendency202122. The findings imply that the variation in intrinsic brain signatures, of the aINS and the NAc may account for the individual differences in risk-taking tendency.…”
mentioning
confidence: 99%